If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-43=-5(6-4x)-(2x-5)
We move all terms to the left:
-43-(-5(6-4x)-(2x-5))=0
We add all the numbers together, and all the variables
-(-5(-4x+6)-(2x-5))-43=0
We calculate terms in parentheses: -(-5(-4x+6)-(2x-5)), so:We get rid of parentheses
-5(-4x+6)-(2x-5)
We multiply parentheses
20x-(2x-5)-30
We get rid of parentheses
20x-2x+5-30
We add all the numbers together, and all the variables
18x-25
Back to the equation:
-(18x-25)
-18x+25-43=0
We add all the numbers together, and all the variables
-18x-18=0
We move all terms containing x to the left, all other terms to the right
-18x=18
x=18/-18
x=-1
| |2z-1|=4 | | 8+5zz=4 | | -57=-y/9 | | -8(2-4f)=-25 | | 6+2(1-9r)=30 | | 0.60x+0.70(60)=0.30(142) | | F(x)=4x+1+2 | | 10.5r-3.8=5.66 | | u/5+16=27 | | r/8=27 | | 2x²+3x-9=0 | | 8x+2=4×-14 | | 8-3x(x-5=2-x(3x-12) | | (2x+3/4)+(x-5)=(x-1/3) | | 14+2y=17 | | 5=(3x+16)/(2) | | 5(2x-3)+4=7x+4 | | -4(3+5n)=-112 | | 2x+3/4+×-5/4=×-1/3 | | 3m+12=11 | | 5=(3x+16)/2 | | 19=1-8r+5r | | 5=(3x=16)/2 | | 5=(3x+16) | | 30p+565=65 | | -1/2(11/6p-5/3)=7/6(p+8/7)-5/4 | | (-44+x)/3=-9 | | 3x=+5=-10 | | -44+x/3=-9 | | 3y+23=7(y+5) | | -2(r-4)=-23 | | 7x-42=3x-24 |